Moral Nimby-ism? Understanding Societal Support for Monetary Compensation to Plasma Donors in Canada - Nicola Lacetera; Mario Macis (Institute of Labor Economics (IZA), 2018)
The growing demand for plasma, especially for the manufacture of therapeutic products, prompts discussions on the merits of different procurement systems. We conducted a randomized survey experiment with a representative sample of 826 Canadian residents to assess attitudes toward legalizing payments to plasma donors, a practice that is illegal in several Canadian provinces. We found no evidence of widespread societal opposition to payments to plasma donors. On the contrary, over 70% of respondents reported that they would support compensation. Our Canadian respondents were more in favor of paying plasma donors elsewhere than in Canada, but the differences were small, suggesting a weak role for moral "NIMBY-ism" or relativism. Moral concerns were the respondents' main reason for opposing payments, together with concerns for the safety of plasma from compensated donors, although most of the plasma in Canada does come from paid U.S. donors. Among those in favor of legalizing payments to donors, the main rationale was to guarantee a higher domestic supply. Finally, roughly half of those who declared to be against payments reported that they would reconsider their position if domestic supply plus imports did not cover domestic demand. Most Canadians, therefore, seem to espouse a consequentialist view on issues related to the procurement of plasma.
Keywords: C01; D63; D64; I11; 330; altruism; plasma donation; ethics